Competing Political Ideologies on the Implementation of Islamic Law in Indonesia: Historical and Legal Pluralist Perspectives - M Arskal Salim GP (AHKAM : Jurnal Ilmu Syariah, 2017)
A contest between different political ideologies took place in the early years after the independence of the Republic of Indonesia. The debate centered on whether the new state would officially apply Islamic law. This article looks at the past events that demonstrated the recurring contest between various ideological camps at different levels and forms. Employing both historical and legal pluralist perspectives, this article ponders several themes at different time and places to show typologies of political ideologies throughout Indonesian modern history. DOI: 10.15408/ajis.v17i2.6233